Treatment of anastomosis stricture after bilateral ileal ureter reconstruction by contralateral retrograde approach: Case report - Somrach Thamtorawat (2018)
© 2016, Medical Association of Thailand. All rights reserved. A 37-year old woman with locally advanced uterine cervical cancer post concurrent chemoradiation, presented with an early anastomotic stricture after ileal ureter replacement due to the ischemic process during the reconstruction procedure. A bilateral ureteral stent was considered in order to relieve the obstructive uropathy. Multiple attempts were made to cannulate the stricture point between the right renal pelvis and ileal ureter, although all of them failed. The percutaneous contralateral nephrostomy tract was accessed and successfully used to perform retrograde approach cannulation. Balloon dilation at the stricture point and ureteral stent placement were successfully performed without any complications. Therefore, the contralateral retrograde approach for ureteral stent placement during bilateral ileal ureter reconstruction has been demonstrated to be both feasible and safe.